Būdvardžio juodas konotacijos - Juzelėnienė, Saulė (Kalbotyra, 2002)
The subject of this study is the connotative meanings of the adjective denoting the colour juodas ‘black’ in Lithuanian. The study has demonstrated that the connotative meaning of the adjective juodas ‘black’ can be only distinguished in the context. In order to successfully define adjectival connotations, it was essential to identify the contextual words which pay a significant role in the realisation of adjective connotations. Adjectives, denoting colour names, usually appear in word combinations alongside with nouns, defining objects with a distinct colour application. In the process of the research, two clear cases have been pointed out: a) the case of the object having the quality “kind of/distinct colour”; b) the case of the object not necessarily having a distinct “kind of/distinct colour” quality, where the object can be of “any colour which is like...” The research of a broader context revealed certain peculiarities, related both to the semantic elements of adjectives (colour names) and to the way they are used in the context, composing a compound seme. The said features made it possible to classify them into peculiar groups. It can be stated that the most common semes, used with adjective juodas ‘black’, are emotional and visual.Thus, it was established, that the colour name juodas ‘black’ has the following connotations: 1. “Associated with misfortune, grief, pain, sadness”; 2. “Associated with evil, something negative”; 3. “Associated with death”; 4. “associated with difficulties, dayto-day cares”.